2021
DOI: 10.1089/ten.tec.2020.0367
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Assessment Requires a Surface Characterization Protocol: Roughness, Friction, and Function

Abstract: The surface of articular cartilage is integral to smooth, low-friction joint articulation. However, the majority of cartilage literature rarely includes measurements of surface characteristics and function. This may, in part, be due to a shortage of or unfamiliarity with fast, nondestructive, and, preferably, noncontact methods that can be applied to large cartilage surfaces for evaluating cartilage surface characteristics. A comprehensive methodology for characterizing cartilage surfaces is useful in determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
2
11
0
1
Order By: Relevance
“…It should be noted that values in the present study were obtained using an LC-MS method, which has been shown to be more precise and accurate than HPLC fluorescence detection methods ( Milićević et al, 2010 ; Wang et al, 2012 ; Bandeira et al, 2013 ; Bielajew et al, 2020 , 2021 ). Pyridinoline crosslink content, for example, has been quantified using LC-MS techniques in bovine articular cartilage, showing crosslink levels of 0.12% of total dry weight, which were on par with values recorded in this study ( Espinosa et al, 2021a ). The posterior region of the medial meniscus contained significantly fewer crosslinks normalized to collagen content compared to the central region ( Figure 6G ), which may contribute to the low radial tensile stiffness in the posterior region.…”
Section: Discussionsupporting
confidence: 79%
“…It should be noted that values in the present study were obtained using an LC-MS method, which has been shown to be more precise and accurate than HPLC fluorescence detection methods ( Milićević et al, 2010 ; Wang et al, 2012 ; Bandeira et al, 2013 ; Bielajew et al, 2020 , 2021 ). Pyridinoline crosslink content, for example, has been quantified using LC-MS techniques in bovine articular cartilage, showing crosslink levels of 0.12% of total dry weight, which were on par with values recorded in this study ( Espinosa et al, 2021a ). The posterior region of the medial meniscus contained significantly fewer crosslinks normalized to collagen content compared to the central region ( Figure 6G ), which may contribute to the low radial tensile stiffness in the posterior region.…”
Section: Discussionsupporting
confidence: 79%
“…This represents a 93% reduction in time. Lastly, we do not expect changes in tissue properties arising from enzymatic degradation or the freeze-thaw cycle in this work given that the joint remained closed prior to testing, cartilage cells are known to very metabolically inactive [66], and that refrigeration is the standard way of storing cartilage tissue [67]. However, this might not be the case when working with large samples, where properties can be affected by testing times; thus, groups working with large tissues and/or requiring a fast turnover will find this decrease in time of utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…The friction coefficients for knee cartilage reported here are comparable to those found in the literature under similar testing conditions. 10,39 To the best of our knowledge, these data do not exist for the facet and SI joints. The friction coefficients from the present study may correlate to the greater range of motion (ROM) required in the knee than in either the facet or SI joints.…”
Section: Discussionmentioning
confidence: 89%